Perlindungan Hukum Terhadap Kebudayaan Melalui World Heritage Centre UNESCO - Dyah Permata Budi Asri (Jurnal Hukum IUS QUIA IUSTUM, 2018)
Legal protection for culture is important because Indonesia has a diversity of cultures which serve as valuable assets. The problems of this study were first, why is the arrangement of Traditional Cultural Expressions in DIY needed in order to provide protection? Second, what is the legal protection of traditional cultural expressions according to UNESCO World Heritage Center? This study aimed to find out about the reasons why the protection for TCE is important and the TCE protection according to UNESCO World Heritage Center. This was a normative legal research using both primary and secondary data. The result of this research concludes that Yogyakarta has carried out efforts to protect and maintain culture because this region has a diversity of cultures so there is a possibility that the ownership of these cultures is claimed by other parties. The local government of Yogyakarta has carried out inventory and documentation efforts, but these efforts are not yet optimal. UNESCO through its World Heritage Center has also performed inventory and documentation on Indonesian cultures. Preventive measures through inventory and documentation are needed to prevent Indonesian cultures from being claimed and exploited without permission by other countries. Until the present time, there are 19 (nineteen) Indonesian cultures that have received UNESCO’s recognition.